Veganist [compact disc, unabridged] : lose weight, get healthy, change the world - Freston, Kathy (Tantor Media, 2011)
Kathy Freston shows listeners how to lean into the veganist life. Effortless weight loss, reversal of disease, environmental responsibility, and spiritual awakening are just a few of the ten profound changes that can be achieved through a gentle switch in food choices.